Praktik Jual Beli Chip pada Game Online Higgs Domino Island sebagai Bentuk Patologi Sosial di Kalangan Mahasiswa - Lutfiah Lutfiah (Yayasan Citra Dharma Cindekia, 2024)
Abstrak The rapid development of digital technology in the Industrial Revolution 4.0 era has contributed to the increasing popularity of online games, including Higgs Domino Island. Although designed as an entertainment platform, the game's chip trading feature has encouraged gambling-related activities among university students. This study aims to analyze the practice of buying and selling chips in Higgs Domino Island as a form of social pathology and to examine its impact on students. This research employed a qualitative descriptive approach. Data were collected through observations and interviews with 20 university students selected using purposive sampling at a university in North Tapanuli. The findings revealed that students played the game for various reasons, including peer influence, entertainment, and the expectation of earning additional income through chip trading. While some participants perceived positive impacts, such as expanding social networks and generating extra income, the negative impacts were more dominant. These included gaming addiction, health and psychological problems, declining academic performance, reduced social interaction, and criminal behavior. The study concludes that the practice of buying and selling chips in Higgs Domino Island has developed into a form of social pathology that requires greater public awareness and stricter government supervision.